Rational use of medicines in older adults: Can we do better during clinical development?. Issue 5 (10th April 2015) - Saeed, MA; Vlasakakis, G; Della Pasqua, O
<x xml:space="preserve">Abstract</x> There is an evidence gap to ensuring safe/effective use of medicines in older adults. Generating clinical data in these patients poses ethical and operational challenges, yielding results that may not be generalizable to the overall population. Modeling and simulation (M&S) is proposed as a basis for assessing the impact of age‐related changes and their clinical implications. M&S can be used in conjunction with bridging and extrapolation to ensure the selection of appropriate dose(s)/regimen(s) in this population.